2011
DOI: 10.1080/00918369.2011.614902
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, Bisexual, and Transgender (LGBT) Physicians' Experiences in the Workplace

Abstract: Little is known about the experiences of lesbian, gay, bisexual, and transgender (LGBT) physicians in the workplace. There is little formal education in medical school about LGBT issues, and some heterosexual physicians have negative attitudes about caring for LGBT patients or working with LGBT coworkers, setting the stage for an exclusive and unwelcoming workplace. The current study used an online survey to assess a convenience sample of 427 LGBT physicians from a database of a national LGBT healthcare organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
5
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(184 citation statements)
references
References 35 publications
5
153
5
11
Order By: Relevance
“…The most common source of heterosexism and/or LGBT discrimination were fellow medical students which was more than twice as common as the next largest group; attending or staff physicians in either a clinical or academic setting. Nonetheless, our results were more positive than previously published studies, where a quarter of LGBT physicians were socially ostracized [14], and a half of general surgery residents had witnessed homophobic remarks by colleagues or staff physicians [31]. This difference between our study and previous literature can be explained by multiple reasons, such as overall societal shift in terms of LGBT rights, as well as cultural and national differences.…”
Section: Discussioncontrasting
confidence: 61%
“…The most common source of heterosexism and/or LGBT discrimination were fellow medical students which was more than twice as common as the next largest group; attending or staff physicians in either a clinical or academic setting. Nonetheless, our results were more positive than previously published studies, where a quarter of LGBT physicians were socially ostracized [14], and a half of general surgery residents had witnessed homophobic remarks by colleagues or staff physicians [31]. This difference between our study and previous literature can be explained by multiple reasons, such as overall societal shift in terms of LGBT rights, as well as cultural and national differences.…”
Section: Discussioncontrasting
confidence: 61%
“…Historically, medical, health and social care professional training programs have contributed to the stigmatization of some sexual and gender identities and 'their' sexual and gender practices. By characterizing LGBT people as pathological, diseased, immoral or "exotic" in teaching, or by erasing them from the curriculum altogether, higher education in these fields does not challenge stigmatizing stereotypes and leaves student practitioners lacking the necessary knowledge and skills to offer inclusive healthcare services (Eliason, Dibble, & Robertson, 2011). For example, Davy and Siriwardena (2012) have suggested that the idiom 'LGBT' may cause practitioners to link diverse healthcare issues together.…”
Section: The Historical Pathologization Of Lgbt People In Medical Hementioning
confidence: 99%
“…Accreditation policies, duties and practitioner competency documents from a range of Councils all stress that the inclusion of diversity and equality issues is fundamental for students' and practitioners' ability to carry out their practice competently (Eliason, Dibble, & Robertson, 2011). Recent competency frameworks have been critiqued as creating production line tick-box exercises, reducing the complex psychosocial roles required of health practitioners, while losing the humane and empathic nature of healthcare practices (Fish & de Cossart, 2007).…”
Section: Professional Competenciesmentioning
confidence: 99%
“…7 Two-thirds of SGM physicians have heard disparaging remarks about SGM at work; one-third have witnessed discriminatory care of an SGM patient; approximately one-quarter have witnessed discrimination against an SGM employee; and approximately one-fifth report experiencing social ostracism because of their SGM identity. 8 Although it is clear that SGM stress extends into the residency application process, [9][10][11] little is known about the relationship between SGM identity and specialty choice. Furthermore, no research to date has examined the association between specialty prestige and SGM specialty choice.…”
Section: Introductionmentioning
confidence: 99%